1987
DOI: 10.1161/01.cir.76.5.1020
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of the Mueller maneuver in man: right and left heart micromanometry and Doppler echocardiography.

Abstract: Ten subjects with normal hemodynamics were studied during elective cardiac catheterization with right and left heart multisensor micromanometry to assess hemodynamic responses to the Mueller maneuver. Simultaneous right and left circulatory hemodynamics and left ventricular, pulmonary arterial, and aortic pressures were recorded, in addition to pulmonary arterial and aortic flow velocities. Steady-state cardiac outputs were determined by thermal dilution. Aortic systolic and mean pressures were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 11 publications
4
58
0
Order By: Relevance
“…3), the pulmonic component of the second sound (simultaneous with the PA dicrotic notch) occurred only after RV pressure had declined nearly to its minimum value, approximately at the level at which the tricuspid valve would have opened. However, it must also be noted that Condos et al (13) reported that, as registered by their catheter-mounted electromagnetic velocity sensor, human PA flow stopped before the dicrotic notch. Thus the length of the RV isovolumic relaxation period remains somewhat controversial.…”
Section: Discussionmentioning
confidence: 98%
“…3), the pulmonic component of the second sound (simultaneous with the PA dicrotic notch) occurred only after RV pressure had declined nearly to its minimum value, approximately at the level at which the tricuspid valve would have opened. However, it must also be noted that Condos et al (13) reported that, as registered by their catheter-mounted electromagnetic velocity sensor, human PA flow stopped before the dicrotic notch. Thus the length of the RV isovolumic relaxation period remains somewhat controversial.…”
Section: Discussionmentioning
confidence: 98%
“…25,26 The forceful ventilatory efforts against upper airway obstruction during apneas result in dramatic shifts in transmural pressures and measurable changes in cardiac chamber dimensions. 27,28 These acute structural changes may promote AF via the triggering of stretch-activated atrial ion channels. 29 In addition, severity of OSA is independently associated with elevated markers of systemic inflammation, including C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…This staging of loop-inloop progression represents the mixed reptilian circulation [28][29][30]. Flows between the split loops calibrate accordingly [31].…”
Section: Mechanism Of Transformationmentioning
confidence: 99%